DETERMINATION OF KIP KULIAH SCHOLARSHIP RECIPIENTS THROUGH PROFILE MATCHING APPROACH AT ROYAL UNIVERSITY - Amin, Muhammad (JURNAL TEKNISI, 2025)
Abstrak: Royal University, located in Kisaran City, North Sumatra, is one of the institutions receiving KIP Scholarship allocations from LLDIKTI Region 1. However, the selection process for scholarship recipients is still conducted manually, making it prone to bias and inaccuracies. This study aims to develop a Decision Support System (DSS) using the Profile Matching method to optimize the recipient selection process. The system evaluates candidates based on five criteria: income, dependents, social status, academic achievement, and housing status. The Profile Matching method calculates gaps between candidate profiles and ideal criteria, assigning weighted scores for ranking. The results show that the system successfully automates and enhances the accuracy, efficiency, and transparency of recipient selection. The final ranking aligns with manual calculations, confirming the system’s reliability. Putri Alya Ramadhani was ranked as the most eligible recipient. The implementation of this system significantly reduces human error and subjectivity, ensuring that scholarships are awarded to truly deserving students. This research demonstrates that a DSS based on Profile Matching can serve as an effective solution for fair and efficient scholarship distribution at Royal University.Keywords: KIP scholarship; profile matching; decision support system. Abstrak : Universitas Royal, yang berlokasi di Kota Kisaran, Sumatera Utara, merupakan salah satu perguruan tinggi yang menerima alokasi beasiswa KIP Kuliah dari LLDIKTI Wilayah 1. Namun, proses seleksi penerima beasiswa masih dilakukan secara manual, sehingga rentan terhadap bias dan ketidaktepatan. Penelitian ini bertujuan untuk mengembangkan Sistem Pendukung Keputusan (SPK) berbasis metode Profile Matching guna mengoptimalkan proses seleksi penerima. Sistem ini menilai kandidat berdasarkan lima kriteria utama: penghasilan, tanggungan, status sosial, prestasi akademik, dan status rumah. Metode Profile Matching menghitung selisih antara profil kandidat dengan kriteria ideal, lalu memberikan bobot untuk menentukan peringkat. Hasil penelitian menunjukkan bahwa sistem ini mampu mengotomatisasi serta meningkatkan akurasi, efisiensi, dan transparansi dalam seleksi penerima beasiswa. Hasil perangkingan sistem sejalan dengan perhitungan manual, yang membuktikan keandalannya, dengan Putri Alya Ramadhani sebagai kandidat terbaik. Implementasi sistem ini secara signifikan mengurangi kesalahan manusia dan subjektivitas, sehingga memastikan beasiswa diberikan kepada mahasiswa yang benar-benar berhak. Penelitian ini membuktikan bahwa SPK berbasis Profile Matching dapat menjadi solusi yang efektif dalam distribusi beasiswa yang lebih adil dan efisien di Universitas Royal.Kata Kunci: beasiswa kip kuliah; profile matching; sistem pendukung keputusan.